(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the occupational health status of nurses at Thong Nhat Hospital. Method: A cross-sectional study was conducted on 383 clinical nurses who had worked at Thong Nhat Hospital for at least 12 months. Use the BAT general burnout assessment questionnaire by Schaufeli W.B and colleagues (2020) for healthcare workers. Results: The prevalence of occupational burnout among nurses was 36.3%. Specifically, 40.2% reported exhaustion, 44.4% emotional impairment, 23.5% cognitive impairment, 26.4% psychological distancing, and 40.5% symptom-related issues. Conclusion: Clinical nurses predominantly experienced a moderate level of occupational burnout, with exhaustion being the most prominent concern.